ANALISIS SWOT STRATEGI PEMASARAN PADA TOKO “HERRY PARABOLA” DI KABUPATEN SUBANG - Annisa Putri A; Euis Apriliana; Hariman Vega; Nova Nursafitri; Yuli Agisna (Gapura (Garba Pembangunan Masyarakat), 2024)
This research is entitled "SWOT Analysis of Marketing Strategy at the "Herry Parabola" Store in Subang Regency". This research aims to analyze the internal and external conditions that influence the marketing strategy at the "Herry Parabola" Store in Subang Regency. The research method used is SWOT analysis which includes analysis of strengths, weaknesses, opportunities and threats at the "Herry Parabola" Store. The research results show that the "Herry Parabola" shop has several advantages such as product quality, strategic location and good reputation. However, this shop also has weaknesses such as limited capital, lack of product innovation, and ineffective promotions. Meanwhile, there are opportunities that can be exploited, such as the growth of the satellite dish industry, technological developments and customer loyalty. On the other hand, this store also faces threats such as intense competition, fluctuations in raw material prices, and changes in consumer preferences. Based on the SWOT analysis, this research produces several business strategies that can be implemented, namely market penetration, product development and diversification strategies. These strategies are expected to help the "Herry Parabola" Store increase its competitiveness and achieve sustainable growth in the future.